Linkages between agriculture and nutrition: implications for policy and research - Kennedy, Eileen T.; Bouis, Howarth E. (International Food Policy Research Institute, 1993)
Whereas there was a tendency in the 1960s to exaggerate the importance of linkages between agriculture and nutrition, during the 1980s such linkages were often belittled. In the earlier decade a stable and sufficiently high level of food production in low-income countries was often considered to be adequate for good nutrition, but through the years the perception grew that agricultural production and food availability were not particularly relevant to favorable nutritional outcomes. These two extreme positions, both of which failed to recognize the important role of agricultural development in improved nutrition, need to be put in perspective.